Computational methods in water resources : proceedings of the XIVth International Conference on Computational Methods in Water Resources (CMWR XIV), June 23-28, 2002, Delft, the Netherlands - Hassanizadeh, S. Majid (Developments in water science ;, 2002)
These volumes contain the proceedings of CMWR2002, which was hosted by the Faculty of Civil Engineering & Geosciences at Delft University of Technology. The interest in this meeting was truly overwhelming: around 230 papers from leading scientists were submitted and accepted for publication in the proceedings. The actual scope of the meeting was much broader than the title "Computational Methods in Water Resources" might suggest. Not only traditional hydrological topics like surface water and groundwater hydrology were covered, but also modern topics like coupled reactive transport, multiphase flow, pore-scale network modeling, remediation techniques, optimization, groundwater-surface water interactions and data assimilation. A quick glance through the Table of Contents of these two volumes immediately shows the richness of the material presented during the four days of the conference. New conceptual models, experimental methods, upscaling techniques and parameter estimation procedures were introduced. Nevertheless, the emphasis was still on the development of new accurate and robust computational techniques